Analysis Techniques for Illicit Bitcoin Transactions - Turner, Adam Brian; McCombie, Stephen; Uhlmann, Allon J. (Frontiers in Computer Science, 2020)
This comprehensive overview of analysis techniques for illicit Bitcoin transactions addresses both technical, machine learning approaches as well as a non-technical, legal and governance considerations. We focus on the field of ransomware countermeasures to illustrate our points.